Model Penilaian Kinerja di Madrasah - Muchlisin, Muchammad Arif (Institut Agama Islam Negeri (IAIN) Tulungagung, 2017)
Teacher performance assessment is an important factor for improving teacher performance. Teacher who have good performance will affect the academic results of students and madrasah. One of the factors influencing teacher performance appraisal is head of madrasah. The assessment model used depends on the experience of the head of the madrasah. The purpose of this study is to investigate how the head of the madrasah in assessing teacher performance and describing the use of teacher performance appraisal model. The research was conducted at Madrasah Aliyah Al-Ikhsan Beji Purwokerto with qualitative research method and descriptive approach. Data were collected by interview, observation, and documentation techniques. The analysis used is qualitative approach with Miles and Huberman model. The result showed that the practice of performance appraisal in Madrasah Aliyah Al-Ikhsan Beji not yet maximal, as for factors that influence the lack of appraiser, assessment aspect, utilization of teacher performance appraisal result. While the model used is Behavior Observation Scale (BOS) and Field Review model.